Perilaku Memilih Santri Pondok Pesantren Pada Pemilihan Presiden 2019 Di Yogyakarta - Muhammad Pengkuh Wedhono Jati (CV. ULIL ALBAB CORP, 2023)
In a period of once every 5 years, Indonesia, which adheres to a democratic system, holds General Elections (PEMILU). Pesantren is an attraction for politicians to win votes, besides the typology of the Nahdlatul Ulama community that is close to the pesantren world is quite feudal so that, always depending on the kyai figure as a role model, this study will focus on how santri make political choices in the 2019 presidential election.